2009
DOI: 10.3892/or_00000661
|View full text |Cite
|
Sign up to set email alerts
|

A new high-performance liquid chromatography method determines low production of 9-β-D-arabinofuranosylguanine triphosphate, an active metabolite of nelarabine, in adult T-cell leukemia cells

Abstract: Abstract. The 9-ß-D-arabinofuranosylguanine (ara-G), an active compound of nelarabine, demonstrates potent cytotoxicity specifically on T-cell malignancies. In cells, ara-G is phosphorylated to ara-G triphosphate (ara-GTP), which is subsequently incorporated into DNA, thereby inhibiting DNA synthesis. Because ara-GTP is crucial to ara-G's cytotoxicity, the determination of ara-GTP production in cancer cells is informative for optimizing nelarabine administration. Here, we developed a new, sensitive isocraticel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…First, to evaluate the antileukemic activity of nelarabine, we investigated ara-G sensitivity of 23 T-ALL cell lines using alamarBlue cell viability assay. The representative dose-response curves are shown in Figure 1B 9 Consistent with above observation, intracellular ara-GTP levels in the three ara-G-sensitive cell lines (DND-41, HPB-ALL, and RPMI-8402) were significantly higher than those in the three ara-G-resistant cell lines (BE-13, LOUCY, and L-KAW) ( Figure 1E). We next investigated the association of cytogenetic abnormalities with ara-G sensitivity in T-ALL cell lines.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…First, to evaluate the antileukemic activity of nelarabine, we investigated ara-G sensitivity of 23 T-ALL cell lines using alamarBlue cell viability assay. The representative dose-response curves are shown in Figure 1B 9 Consistent with above observation, intracellular ara-GTP levels in the three ara-G-sensitive cell lines (DND-41, HPB-ALL, and RPMI-8402) were significantly higher than those in the three ara-G-resistant cell lines (BE-13, LOUCY, and L-KAW) ( Figure 1E). We next investigated the association of cytogenetic abnormalities with ara-G sensitivity in T-ALL cell lines.…”
supporting
confidence: 84%
“…These results suggested that combined ENT1 and DCK gene expression levels are highly associated with ara‐G sensitivity in T‐ALL cell lines. We also quantified intracellular ara‐GTP levels in six representative cell lines after a 5‐hour exposure to 10 μM of ara‐G using high‐performance liquid chromatography analysis . Consistent with above observation, intracellular ara‐GTP levels in the three ara‐G‐sensitive cell lines (DND‐41, HPB‐ALL, and RPMI‐8402) were significantly higher than those in the three ara‐G‐resistant cell lines (BE‐13, LOUCY, and L‐KAW) (Figure E).…”
supporting
confidence: 80%
“…The acid‐soluble fraction (nucleotide pool) was extracted from HL‐60 cells or HL‐60/ara‐C60 cells (1 × 10 6 /mL, 10 mL), treated or untreated. High performance liquid chromatography was then used to determine intracellular ara‐CTP and ara‐GTP as described in previous studies …”
Section: Methodsmentioning
confidence: 99%
“…High performance liquid chromatography was then used to determine intracellular ara-CTP and ara-GTP as described in previous studies. (12,15,25) Nucleoside transport capacity. To evaluate the capacity of membrane nucleoside transporters, ara-C uptake was quantified using the method of Wiley et al with slight modifications.…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the cell proliferation, a sodium 3'-{1-[(phenylamino)-carbonyl-3,4-tetrazolium]}-bis(4-methoxy-6-nitro) benzene sulfonic acid hydrate (XTT) assay was performed according to the manufacturer's instructions (Roche, Indianapolis, IN, USA) with slight modifications (19). In brief, 1 ml of a cell suspension (5x10 4 /ml) was incubated for 24 h in a 24-well plate, followed by the addition of a 10-μl aliquot of CPT solution at various concentrations.…”
Section: The Alkaline Single Cell Gel Electrophoresis (Comet) Assaymentioning
confidence: 99%